Estimation of vitamin D levels in patients with pemphigus vulgaris. (10th May 2013) - EL‐Komy, M.H.M.; Samir, N.; Shaker, O.G.
Abstract Background Keratinocyte acantholysis as a result of pathogenic Dsg3‐antibodies production by B cells leads to Pemphigus vulgaris (PV). Vitamin D, through its participation in several immune modulatory functions including B cells apoptosis, Th2 cell differentiation, apoptotic enzyme regulation and Tregs functions, may be actively involved in the immune regulation of PV. Objective To evaluate Vitamin D status in PV patients in comparison to controls in an attempt to determine its role in this autoimmune disease. Methods Using ELISA technique, 25‐hydroxyvitamin D (25OHD) was determined for 34 pemphigus vulgaris patients and 20 healthy volunteers. Phosphorus and parathormone were also determined in the patient group. Results 25OHD was significantly lower in patients than controls (P = 0.008). There was a statistically significant difference between both groups regarding suboptimal Vit. D levels (P = 0.007). Conclusion Patients with PV have significantly lower serum vitamin D levels in comparison to controls and that these low levels were not related to age, BMI or pattern of sun exposure. The associated Vitamin D insufficiency in patients with PV may possibly exacerbate their disease through various immune related mechanisms.